Standardization Of Size, Shape And Concentration Of Nanoparticle For Plant Application (Applied Biological Research, 2012)
A number of experiments were conducted to know the optimum size,  shape and concentration of nanoparticles to be sprayed to plants for  better penetration and translocation. Nanoparticles were capable of  penetrating living plant tissues when sprayed on plant leaves, and  migrated from leaves to different parts of plant. The results demonstrated  14.7% nanoparticles loss when sprayed by aerosol technique (using  nebulizer) as compared to 32.5% loss by normal sprayer. Low  concentration (< 5 ppm) of nanoparticles were better absorbed and  translocated through plant leaves. Higher the particle size lower was nanoparticle penetration. Particle size
Keywords: Concentration; nanoparticle; shape; size; transportation